Learning Style and Performance in Mathematics of Senior High School Students Using Online Blended Learning Modality - Magbanua, Claire C.; Bearneza, Francis Jose D. (Technium Social Sciences Journal, 2023)
Teaching and learning mathematics are a significant concern in any educational system and became more challenging during the pandemic when an online, blended learning modality is being implemented. Hence, this descriptive-comparative-correlative research study sought to determine the dominant learning style and level of performance in general mathematics of the 222 senior high school students using online, blended modality during the school year 2021-2022 when they are grouped according to sex and tracks. The researcher made use of a standardized Learning Style inventory and a researcher-made test questionnaire which has a content-validity index of 1.00 indicating a high validity and a Cronbach’s alpha of 0.901 which indicates a very high reliability. Results showed that the dominant learning style of the Grade 11 students is auditory, while their performance level in General Mathematics is average; there is a significant difference in their performance in General Mathematics when students are grouped according to tracks; and there is no significant difference between the learning style and level of performance in General Mathematics of the senior high school students [X2(220)=0.335,p=0.656]. Thus, students’ learning styles is not a sole factor on how well they perform in general Mathematics. There might be other aspects such as study habits, math anxiety, grit, and the like which can be further investigated by future researchers.